Fostering African-American Improvement in Total Health (FAITH!): An Application of the American Heart Association’s Life’s Simple 7™ among Midwestern African-Americans - Brewer, LaPrincess C. (J Racial Ethn Health Disparities, 2016)
OBJECTIVE: African-Americans have a strikingly low prevalence of ideal cardiovascular health metrics of the American Heart Association’s Life’s Simple 7 (LS7). This study was conducted to assess the impact of a community-based cardio-vascular disease prevention intervention on the knowledge and achievement of cardiovascular health metrics among a marginalized African-American community. METHODS: Adult congregants (n = 37, 70 % women) from three African-American churches in Rochester, MN, participated in the Fostering African-American Improvement in Total Health (FAITH!) program, a theory-based, culturally-tailored, 16-week education series incorporating the American Heart Association’s LS7 framework. Feasibility testing included assessments of participant recruitment, program attendance, and retention. We classified participants according to definitions of ideal, intermediate, and poor cardiovascular health based on cardiac risk factors and health behaviors and calculated an LS7 score (range 0 to 14) at baseline and post-intervention. Knowledge of cardiac risk factors was assessed by questionnaire. Main outcome measures were changes in cardiovascular health knowledge and cardiovascular health components related to LS7 from baseline to post-intervention. Psychosocial measures included socioeconomic status, outlook on life, self-reported health, self-efficacy, and family support. RESULTS: Thirty-six out of 37 recruited participants completed the entire program including health assessments. Participants attended 63.5 % of the education series and attendance at each session was, on average, 62 % of those enrolled. There was a statistically significant improvement in cardiovascular health knowledge (p < 0.02). A higher percentage of participants meeting either ideal or intermediate LS7 score categories and a lower percentage within the poor category were observed. Higher LS7 scores correlated with higher psychosocial measures ratings. CONCLUSIONS: Although small, our study suggests that the FAITH! program is a feasible, community intervention promoting ideal cardiovascular health that has the potential to improve cardiovascular health literacy and LS7 among African-Americans.